Bioethics in law - Spielman, Bethany, 1952- (Totowa, N.J. : Humana Press, 2007)
"This volume is the first to analyze how and to what extent bioethics considerations influence today's judges. Previous books have attended to the law that governs bioethics problems, but Bioethics in Law is the first to examine when and how bioethical issues impact judicial reasoning and decision-making." "The author undertakes careful analysis of health care committee recommendations, institutional review board determinations, bioethics commission reports, bioethics research materials, briefs of bioethics amicus curiae, and bioethics expert testimony that has been used in legal proceedings during the last decade. Through such examination, Bioethics in Law is able to offer critical insight into the ways that judges have invited, accepted, relied on, followed, critiqued, ignored, rejected, overridden, transformed, and otherwise responded to bioethics communications. This volume is the on the cutting-edge of the relationship of bioethics to law, and explores how law receives, assesses, and uses bioethics. Unlike previous treatments, which perceive the relationship between law and bioethics in an abstract or idealized sense, this book presents actual communications that have found their way to law, and then analyzes their effect on judicial outcomes."--Jacket.
How does bioethics help judicial reasoning? -- Health care ethics committee determinations -- Institutional review board determinations -- Bioethics commission reports -- Bioethics scholarship -- Reliability of bioethics testimony : general acceptance -- Reliability of bioethics testimony : peer review and publication -- Reliability of bioethics testimony : experience.
Includes bibliographical references and index.
Keywords: Medical laws and legislation -- United States; Judicial process -- United States; Medical jurisprudence -- United States; Bioethics -- United States; Bioethics; Medical jurisprudence; Medical laws and legislation; Bioethical Issues -- legislation & jurisprudence; Bioethics; Ethics, Medical; United States; United States